Developing The Spirit of Leadership And The Spirit of Solidarity As Well As The Existence Of The Student Association - Daulat Nathanael Banjarnahor; Firinta Togatorop; David Banjarnahor; Vesy Morayva Sitanggang; Doris Yolanda Saragih; Pangidoan Adventus Ambarita (Marsiurupan: Journal of Community Development and Empowerment, 2026)
The purpose community Service Program is grow soul leadership transformative, strengthening Spirit solidarity, as well as confirm return the existence of HMPS as receptacle development character And competence students. Method implementation designed in a participatory manner through three stages main, namely lecture interactive about draft leadership And solidarity, simulation studies case based group For hone ability solution problem collective, and game quiz educative as evaluation mastery material. Participants activity is new students of the Program Studies Education Citizenship And Students who have not follow Exercise Base Leadership Results activity show existence improvement significant to understanding participant to style leadership situational, awakening awareness collective will importance solidarity organic, and emergence commitment together For revitalize program Work set. Simulation studies case succeed bring up strategy collaborative in finish conflict internal And external organization. Quiz evaluation show average score mastery material reached 75 percent. Discussion reflective post activity indicates growing sense of belonging And optimism participant to the existence of HMPS in time coming